Non-Parametric Reconstructions of Cosmic Curvature - Dias, Mariana; Bengaly, Carlos; Cunha, Antônio; Gonçalves, Rodrigo; Morais, Jonathan (Cadernos de Astronomia, 2026)
Work presented at the event As Astrocientistas: III Encontro Brasileiro de Meninas e Mulheres da Astrofísica, Cosmologia e Gravitação, held between March 31 and April 4, 2025.